Analisis Implementasi Sistem Penilaian pada Kurikulum Merdeka di SDN Pondok Jengkol Kabupaten Tangerang - Magdalena, Ina; Anisa, Dela; Salsabila, Nada; A, Tarisa Amalia (Lembaga Yasin AlSys, 2023)
The final assessment in the SDN environment isbthe goalkof thislstudy, whichgaims tojdetermine whether or not the implementation of learning design is successful. An implementation is one that is meticulously planned and executed. A straightforward definition of the term